Differences and resemblances in banding patterns and ribosomal DNA distribution in four species of Paullinieae tribe (Sapindaceae) - Urdampilleta, Juan Domingo (2008)
The tribe Paullinieae (Sapindaceae) is exclusively neotropically distributed, and is characterized by apomorphic characters and considered a monophyletic natural group. Recently explored cytogenetical aspects suggest that the disploid chromosomal reduction, the increase in the chromosomal size and the diversification of highly repetitive DNA sequences are associated with the karyotyp-ic evolution of this tribe. This work compares patterns of chromosome banding and the distribution of ribosomal DNA 18S-5.8S-26S in Cardiospermum grandiflorum Sw., Pullinia elegans Cambess., Urvillea chacoensis Hunz. and U. ulmacea Kunth. The studied species share the presence of a pattern of terminal C-Giemsa bands, differentiated for characteristics of heterochromatic regions. Terminal AT-rich bands occurred in C. grandiflorum (2n=2x=20) and U. chacoensis (2n=2x=22). Differing from the others, U. chacoensis presented prominent bands in the majority of chromosomes. The polyploid cytotype of U. ulmacea (2n=8x=88) possessed terminal bands CMA+ and DAPI+, forming heterochromatic blocks constituted by GC- and AT-rich repetitive DNA. On the other hand, P. elegans (2n=2x=24) presented a pattern of neutral bands after staining with CMA3/DAPI. The presence of GC-rich regions associated with 45S rDNA sites was a common characteristic in the studied species, nevertheless, variations in the NOR number might be useful for the differentiation of some species. Our results on karyological differences and resemblances of the studied species are discussed in relation to the systematics of the Paullinieae tribe. © 2008 The Japan Mendel Society.